The Use of Portfolios in the Assessment of Literature Learning in EFL Classes The Case Study of Master One Teachers and Students at the Department of English-University of Laghouat - Kraim ,Tasnim Fatima Zahra; Boumediene, Houda (Faculty of Letters and Foreign Languages Department of English, 2018)
This study aims at investigating the effectiveness of using portfolios in the assessment of literature. In order to reach this objective, a descriptive study was conducted. A questionnaire was used in order to collect data. The sample consisted of (50) participants from Master One students of English, and (7) teachers of English Literature from the department of English at Amar Thelidji University in Laghouat, Algeria. This study took place during the second semester of the academic year 2017-2018. The findings of the data analysis yielded positive results concerning portfolios’ use in the assessment of literature learning. Despite the fact that portfolios were used only in one module with one teacher as the results indicated, yet, students after using their portfolios were able to develop their skills in analyzing literary texts according to different literary elements, as they improved their writing skills. The results of the study demonstrated that both teachers and students attribute positive comments for integrating portfolio assessment as an effective tool in language teaching and learning. Also, they strongly appreciate the use of portfolios as alternatives to traditional instruments like tests and exams.